PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. TRAKTOR NUSANTARA CABANG PEKANBARU - Ikmal Kahfi Husada; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of organizational culture and work environment on employee job satisfaction in PT. Traktor Nusantara Pekanbaru Branch. The independent variable consists of organizational culture (X1) and work environment (X2). Meanwhile, what is used as the dependent variable (Y) is job satisfaction. This study uses a questionnaire with a measurement scale using a Likert scale. The analysis technique used is simple linear regression, multiple linear regression, coefficient of determination test, t test, and f test. Data analysis using linear regression analysis with the help of SPSS 25 software.            The population in this study were 40 employees of PT. Traktor Nusantara Pekanbaru Branch where the whole use the sample using the census method. The test results show that organizational culture has a positive and significant effect on job satisfaction, work environment has a positive and significant effect on job satisfaction, and organizational culture and work environment simultaneously influence job satisfaction. Keywords : Organizational Culture, Work Environment, Job Satisfaction.